Government debt, land financing and distributive justice in China. (August 2021) - Cai, Meina; Fan, Jianyong; Ye, Chunhui; Zhang, Qi
Massive funds that are necessary to finance China's capital-intensive urbanisation are channelled through Local Government Financing Vehicles (LGFVs), which are established by local governments to circumvent the prohibition on borrowing. This study examines LGFV development and how this land financing development strategy influences villagers. We argue that China's discriminatory land property system and the feature of land being a captive asset allow local governments to transfer their debt pressure to land-losing villagers. Specifically, we find that more indebted local governments take a more extractive approach by paying land-losing villagers less compensation, suggesting the intrinsic connections of the local state, land-centred local public finance and society in China's urban transformation. Our findings suggest that local governments can be developmental and predatory at the same time. Our arguments are developed using data that combine a self-compiled data set on LGFV debt with the China Household Finance Surveys. It systematically examines the connections between land financing via LGFVs and land-losing villagers. It contributes to a better understanding of the debt-fuelled urbanisation in China and, more broadly, of how the state intervenes in the economy and impacts distributive justice in developing and transition economies.